Allosteric control of internal electron transfer in cytochrome cd(1) nitrite reductase - Farver, Ole (National Academy of Sciences, 2003)
Cytochrome cd(1) nitrite reductase is a bifunctional multiheme enzyme catalyzing the one-electron reduction of nitrite to nitric oxide and the four-electron reduction of dioxygen to water. Kinetics and thermodynamics of the internal electron transfer process in the Pseudomonas stutzeri enzyme have been studied and found to be dominated by pronounced interactions between the c and the d(1) hemes. The interactions are expressed both in dramatic changes in the internal electron-transfer rates between these sites and in marked cooperativity in their electron affinity. The results constitute a prime example of intraprotein control of the electron-transfer rates by allosteric interactions.